Facing the Other : John Paul II, Levinas and the Body. - Zimmermann, Nigel (James Clarke & Co, 2016)
A study of the theological and ethical significance of the body, creatively bringing into dialogue the writings of Karol Wojtyla and Emmanuel Levinas.